Myosin VIIA Is Required for Aminoglycoside Accumulation in Cochlear Hair Cells - Richardson, G. P. (J Neurosci, 1997)
Myosin VIIA is expressed by sensory hair cells and has a primary structure predicting a role in membrane trafficking and turnover, processes that may underlie the susceptibility of hair cells to aminoglycoside antibiotics. [(3)H]Gentamicin accumulation and the effects of aminoglycosides were therefore examined in cochlear cultures of mice with different missense mutations in the myosin VIIA gene, Myo7a, to see whether myosin VIIA plays a role in aminoglycoside ototoxicity. Hair cells from homozygous mutant Myo7a(sh1) mice, with a mutation in a nonconserved region of the myosin VIIA head, respond rapidly to aminoglycoside treatment and accumulate high levels of gentamicin. Hair cells from homozygous mutantMyo7a(6J) mice, with a mutation at a highly conserved residue close to the ATP binding site of the myosin VIIA head, do not accumulate [(3)H]gentamicin and are protected from aminoglycoside ototoxicity. Hair cells from heterozygotes of both alleles accumulate [(3)H]gentamicin and respond to aminoglycosides. Although aminoglycoside uptake is thought to be via apical surface-associated endocytosis, coated pit numbers on the apical membrane of heterozygous and homozygousMyo7a(6J) hair cells are similar. Pulse–chase experiments with cationic ferritin confirm that the apical endocytotic pathway is functional in homozygousMyo7a(6J) hair cells. Transduction currents can be recorded from both heterozygous and homozygousMyo7a(6J) hair cells, suggesting it is unlikely that the drug enters via diffusion through the mechanotransducer channel. The results show that myosin VIIA is required for aminoglycoside accumulation in hair cells. Myosin VIIA may transport a putative aminoglycoside receptor to the hair cell surface, indirectly translocate it to sites of membrane retrieval, or retain it in the endocytotic pathway.